2015
DOI: 10.1159/000430988
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Signal-to-Cutoff Ratio of Hepatitis C Virus Antibody Assay in Predicting HCV Viremia among Hemodialysis Patients

Abstract: Background: Hepatitis C virus (HCV) infection is a common cause of acute and chronic hepatitis among the hemodialysis population. To prevent cross infection between hemodialysis patients during the hemodialysis procedure, routine screening of anti-HCV antibody is recommended. However, a reactive anti-HCV EIA test is not equal to active HCV infection. An expensive RT-PCR study is required to confirm HCV viremia. This will significantly increase the cost burden because payment for each hemodialysis treatment is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The higher OD value from the S/CO ratio also correlated with the likelihood of an active HCV infection. In contrast, a lower S/CO ratio was predictive of HCV RNA negativity [ 22 ] as HCV RNA was only detected in 2 samples in the low S/CO-ratio group (7%). The latter may be due to several reasons including spontaneous clearance of previous HCV exposure, low viral load, or occult infection [ 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher OD value from the S/CO ratio also correlated with the likelihood of an active HCV infection. In contrast, a lower S/CO ratio was predictive of HCV RNA negativity [ 22 ] as HCV RNA was only detected in 2 samples in the low S/CO-ratio group (7%). The latter may be due to several reasons including spontaneous clearance of previous HCV exposure, low viral load, or occult infection [ 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a cutoff S/Co ratio of 24, they could confirm HCV viremia with a sensitivity and positive predictive value (PPV) of 91.7%, specificity and negative predictive value (NPV) of 82.4%. The sensitivity, specificity, PPV, and NPV were found to be 86.1%, 94.1%, 96.9%, 76.2% respectively when S/Co ratio was set 44 as cutoff [26].…”
Section: Discussionmentioning
confidence: 97%
“…Pan et al [25] used Elecsys Anti-HCV II (Roche Diagnostics) screening test and confirmed the results with RIBA and found the S/Co ratio as 12.27 with 97.8% sensitivity and 86% specificity. Kao et al [26] examined the S/Co ratio for AxSYM Microparticle Enzyme Immunoassay (MEIA) (Abbott Laboratories) using PCR for confirmation and found the S/Co ration optimal at 24 and 44. Using a cutoff S/Co ratio of 24, they could confirm HCV viremia with a sensitivity and positive predictive value (PPV) of 91.7%, specificity and negative predictive value (NPV) of 82.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, simpler, less expensive, and more rapid methods and/or algorithms are required for the quantification of HCV viremia . Recently, Kao et al used the signal‐to‐cut (S/CO) ratio of anti‐HCV antibody to predict HCV viremia, among a hemodialysis population. They demonstrated that a cut‐off S/CO ratio of >65 had 100% specificity, 80.1% sensitivity, and 100% positive predictive value for discriminating HCV viremia from non‐viremia.…”
Section: Discussionmentioning
confidence: 99%